Concurrent right atrial isomerism, complete atrioventricular septal defect, and single ventricle in an L-transposition of great arteries patient complicated by brain abscess. (25th June 2019) - Yonas, Emir; Pranata, Raymond; Nusarintowati, Nuvi
Abstract: We present a case of an 11-year-old Indonesian female who was referred to our facility after surgical excision of brain abscess. The patient has been previously diagnosed with right atrial isomerism, complete atrioventricular septal defect, and L-Transposition of great arteries. Multiple staged surgeries are required for the management of this condition.